How myth became history : Texas exceptionalism in the borderlands - Dean, John Emory (University of Arizona Press, 2016)
"The book explores how border subjects have been created and disputed in cultural narratives of the Texas-Mexico border, comparing and analyzing Mexican, Mexican American, and Anglo literary representations of the border"--Provided by publisher.